Optimising conservation breeding efforts: investigating the effects of ultraviolet radiation on colouration of the northern corroboree frog (Pseudophryne pengilleyi) - McFadden, Michael S.; Silla, Aimee J.; Kelleher, Shannon R.; Endler, John. A.; Landler, Lukas; Byrne, Phillip G. (Frontiers in Amphibian and Reptile Science, 2025)
As the global biodiversity crisis worsens, Conservation Breeding Programs (CBPs) are proving critical for safeguarding threatened species, yet the influence of the ex situ rearing environment on phenotypic expression remains poorly understood. For amphibian CBPs, understanding the impacts of ultraviolet radiation (UVR) on various fitness-determining traits has come into focus. The aim of the present study was to investigate the effect of ecologically-relevant UVR levels on post-metamorphic colouration in the critically endangered northern corroboree frog (Pseudophryne pengilleyi). This species is characterised by striking lime/yellow and black colouration and shows inter-individual colour variation, but potential impacts of UVR are yet to be investigated. UVR was provided at one of two ecologically appropriate levels: lower UVR (∼0.2 UVI) and higher UVR (∼0.7 UVI). Each treatment included 10 replicate containers housing five frogs, and individuals remained under the same conditions for an experimental period of 16 weeks, spanning the first growth phase prior to hibernation. Frogs in the higher UVR treatment did not display significant differences in hue, though displayed slightly lower chroma (significant at weeks 4 and 12), and slightly higher luminance (significant at week 12 and 16). Underpinning these differences, frogs in both treatment groups displayed a significant change in colour during post metamorphic development. Hue became more yellow-green shifted, and there was an increase in luminance, chroma, and the proportion of yellow colouration. These findings indicate that the range of UVR levels we tested induced minor yet detectable colour changes, and that corroboree frogs display ontogenetic colour change. We conclude that the UVR levels in the range of ∼0.2-0.7 UVI do not cause extreme colour change in northern corroboree frogs and discuss the value of this knowledge for refining CBPs for corroboree frogs and other threatened amphibians.